PERENCANAAN USAHA MIKRO KECIL (UMK) BAGI BISNIS PEMULA - casmudi casmudi; Sugianto Sugianto (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2021)
Abstract The background of the research of micro business owners departed from recklessness, the urgency of economic conditions. The purpose of this study is to describe the efforts of micro group entrepreneurs in operating their businesses. The focus of this research is the operationalization of micro entrepreneurs (UM). The research method uses a case study approach, the research subjects are determined with the criteria that micro business actors have been operating for at least 3 years and have bright prospects in their business class. Collecting data through structured and in-depth interviews with 5 micro group entrepreneurs. The descriptions are 1) cricket cultivators, 2) catfish cultivators, 3) ornamental plant cultivators, 4) hydroponic gardens, and 5) managers of fishing ponds and fish nurseries. The results of the study (1) Aspects of business planning 60% of entrepreneurs collect initial data and 40% of business actors do not do it. (2) The collected data is filtered by 40% of business actors, and 60% has not filtered the data. The job description is detailed as much as 40% of business actors and the remaining 60% does not describe. (3) The indicators for establishing policies and program preparation have not been carried out by these business actors. (4) the results of the analysis of the business canvas using 13 criteria for hydroponic business actors to reach the highest target of 83.66, fishing pond business actors 66.67 cricket cultivation actors 58.33 ornamental plant cultivation actors 50.00 and catfish cultivation 50.00. Abstrak Latar belakang penelitian para pemilik usaha mikro berangkat dari tekad, terdesaknya kondisi ekonomi. Tujuan penelitian ini mendiskrepsikan upaya usahawan kelompok mikro-kecil dalam menyusun perencanaan usahanya. Fokus penelitian ini adalah perencanaan oleh usahawan mikro-kecil (UMK). Metode penelitian Kualitataitf dengan pendekatan studi kasus, subyeknya penelitian ditetapkan dengan kriteria pelaku usaha mikro telah beroperasi minimal 3 tahun dan memiliki prospek cerah di kelas usahanya. Pengumpulan data melalui wawancara terstrtuktur dan mendalam kepada usahawan kelompok mikro berjumlah 5 orang. Rianciannya 1) pembudaya jangkrik, 2) pembudidaya ikan lele, 3) pembudidaya tanaman hias, 4) kebun hidroponik, dan 5) pengelola kolam pemancingan dan pembibitan ikan. Hasil penelitian (1) Aspek perencanaan usaha 60% wirsusahawan menghimpun data awal dan 40% pelaku usaha tidak melakukannya. (2) Data terhimpun dilakukan penyaringan 40% pelaku usaha, dan 60% belum belum menyaring data. job description diruaikan detail sebanyak 40% pelaku usaha dan 60% sisanya tidak menguraikan. (3) Indikator menetapkan kabijakan dan penyusunan program belum di lakukan oleh para pelaku usaha ini. (4) hasil analisis canvas bisnis menggunakan 13 kriteria pelaku usaha hidroponik mencepai sasaran tertinggi sebesar 83,66, pelaku usaha kolam pemancingan 66,67 pelaku budidaya jangkrik 58,33 pelaku budidaya tanaman hias 50,00 terakhir budidaya ikan lele 50,00. Kata kunci : Pelaku bisnis Mikro Kecil, Perencanaan usaha, dan Operasional bisnis